The effects of benralizumab on lung volumes and airway resistance in severe eosinophilic asthma: a real-world study - Gerardo, António Madeira (2024)
Introduction: Add-on biological monoclonal antibodies such as benralizumab (anti-IL-5Ra) are recommended by international guidelines to reduce exacerbations in severe eosinophilic asthma (SEA). However, few studies have assessed the impact of these therapies on lung function-related outcomes. Our goal was to evaluate the effectiveness of benralizumab on lung function, including lung volumes and airway resistance, in SEA patients in Portugal. Methods: This was a real-world, observational, prospective, multicentric study including adult patients diagnosed with SEA (January-June 2023). Spirometry and plethysmography were performed at baseline (T0) and after six months of treatment (T6) with benralizumab to assess: total lung capacity (TLC), residual volume (RV), forced expiratory volume in one second (FEV1), forced vital capacity (FVC), mean forced expiratory flow between 25% and 75% of FVC (mFEF-25/75), intrathoracic gas volume (ITGV), and respiratory airway resistance (Raw). Descriptive statistics (with categorical variables described as frequencies and continuous values as mean and standard deviation (SD)) and paired t-test and Cohen's d effect size were calculated (analyses performed in StataCorp v.15.1; StataCorp LLC, TX, USA). Results: Overall, 30 SEA patients were evaluated, mostly women (n=18, 60.0%), with atopy (n=22, 73.3%), a mean age of 58.4 years (SD 11.7), and assisted by pulmonology (n=19, 63.3%) or immunology-allergology (n=11, 36.7%) services. Mean eosinophilia at baseline was 1103.57 cells/mcL (SD 604.88; minimum-maximum 460-2400); after the use of benralizumab, the count dropped to zero. After six months of treatment, a significant increase (p<0.0001) in FVC (15.3%), FEV1 (22.6%), and mFEF-25/75 (17.7%) were observed from baseline (Cohen's d between 0.78 and 1.11). ITGV, RV, RV/TLC, and Raw significantly decreased (p<0.0001) during the study period (-17.3%, -29.7%, -8.9%, and -100.6%, respectively) (Cohen's d between -0.79 and -1.06). No differences in TLC were obtained (p=0.173). No differences between sexes were observed for any measure. Patients with more significant eosinophilia (>900 cells/mcL count; n=15) presented better responses in FEV1 (p=0.001) and mFEF-25/75 (p=0.007). Conclusions: A notable eosinophil depletion with add-on benralizumab led to significant improvements in SEA patients' respiratory function (static lung volumes and airway resistance) in real-world settings after six months. The significant deflating effect of benralizumab on patients' hyperinflated lungs led to enhanced expiratory flow (increased FEV1 and mFEF-25/75) and air trapping (decreased RV/TLC), suggesting this antibody improves bronchial obstruction, lung hyperinflation, and airway resistance. Further studies in a larger population are required to confirm these findings.